2021
DOI: 10.1021/acs.langmuir.1c00851
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Torque on a Particle Rotating at an Interface

Abstract: Small particles attach to liquid−fluid interfaces due to capillary forces. The influence of rotation on the capillary force is largely unexplored, despite being relevant whenever particles roll at a liquid− fluid interface or on a moist solid. Here, we demonstrate that due to contact angle hysteresis, a particle needs to overcome a resistive capillary torque to rotate at an interface. We derive a general model for the capillary torque on a spherical particle. The capillary torque is given by M = γRLk(cos Θ R −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Because rotation causes a decrease in the detachment force, it may, at first, seem that inducing the rotation of particles could be a useful way to facilitate the detachment of particles from interfaces. However, this may not be economical from an energetic perspective because in order to rotate a particle against an interface, energy needs to be supplied to overcome resistive capillary torque (described in ref 19). Capillary torque is due to the fact that the liquid−fluid interface is not axisymmetric about the center of a rotating particle.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because rotation causes a decrease in the detachment force, it may, at first, seem that inducing the rotation of particles could be a useful way to facilitate the detachment of particles from interfaces. However, this may not be economical from an energetic perspective because in order to rotate a particle against an interface, energy needs to be supplied to overcome resistive capillary torque (described in ref 19). Capillary torque is due to the fact that the liquid−fluid interface is not axisymmetric about the center of a rotating particle.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…23−28 On one side of the rotational axis, the particle rolls out of the liquid, and therefore, the contact angle corresponds to the receding contact angle, whereas on the opposite side the contact angle corresponds to the advancing contact angle, Θ A . 19 In general, Θ A differs from Θ R due to chemical and topographical inhomogeneities on the particle and/or adaptation of the particle to the liquid. 29,30 Consequently, eq 1 does not hold for a rotating particle and should be modified.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact dynamic effects, such as contact angle hysteresis or contact line pinning, are certainly important when capillary bonds are stretched or compressed but can also arise under rotation, as shown in Figure 5 [60]. Naga et al recently showed that a particle situated at an interface between two phases can experience similar effects as a liquid droplet sliding across a surface or a sphere rotating above a surface.…”
Section: Nonideal Wettingmentioning
confidence: 99%
“…Contact dynamical effects, such as contact angle hysteresis or contact line pinning, are certainly important when capillary bonds are stretched or compressed, but can also arise under rotation, as shown in Figure 5. [57] Naga et al recently showed that a particle situated at an interface between two phases can experience similar effects as a liquid droplet sliding across a surface or a sphere rotating above a surface. The resulting force or torque forms a barrier similar to an activation energy that needs to be overcome in order to reach a state of unhindered sliding or rotation.…”
Section: Non-ideal Wettingmentioning
confidence: 99%